E - COMMERCE AND TAXATION - Beriwala, Dr. Prachi; Sowmiya, Dr. G.; Gupta, Dr. Prashant (The journal of contemporary issues in business and government, 2022)
Obaidat, M. S., & Lorenz, P. (2016). Short form of electronic commerce is e- commerce, it is a type of innovative business model where individual or group or a firm can buy and sell on electronic network with support of internet. Another name of e-commerce is online commerce, web commerce, e-retail, etail and e-comm. But e-tail refers to any transactional processes around retail.